Perceptions of orthodontically treated smile esthetics: a comparative evaluation of orthodontists, general dentists, and laypersons in Erbil city. - Isra Dilshad Rostum; Zana Omer (Erbil Dental Journal)
Background and Objective: Knowing the perception of a layperson will help an orthodontist to have an idea about acceptable smiles in our community. The study is aimed to evaluate and compare the smile perception among orthodontists, general dentists, and laypersons in a sample of Erbil city.